The use of mouthwash containing trimetaphosphate as an adjunct therapy to fluoridated toothpaste reduces enamel demineralization - Gruba, Amanda Scarpin; Nunes, Gabriel Pereira; Danelon, Marcelle; Gonçalves, Francyenne Maira Castro; de Toledo, Priscila Toninatto Alves; Ferreira, Mayra Fernanda; Poli, Maria Clara Faria; Delbem, Alberto Carlos Botazzo (Journal of dentistry, 2024)
•No treatment prevented demineralization, but FT + MW 100F resulted in lower%SH and ΔKHN.•FT + MW-TMP association led to less mineral loss in the deeper region of the dental enamel.•FT + MW-TMP association presented the highest increase in calcium and phosphorus in enamel.•The FT + MW 100F - TMP treatment should be investigated in situ and clinical studies. The decline in dental caries has been attributed to the widespread use of fluoride (F). Two forms of presentation are fluoridated toothpaste (FT) and mouthwash (MW), widely used by the population. This study aimed to evaluate in vitro the effects of combining FT and MW, whether supplemented with sodium trimetaphosphate (TMP) or not, on dental enamel demineralization. Bovine enamel blocks (n = 60) were selected based on initial surface hardness (SHi) and divided into 5 experimental groups (n = 12 each): I) Placebo Toothpaste (without F/TMP); II) 1100 ppm F Toothpaste (FT); III) 1100F associated with a MW at 100 ppm F (FT + MW 100F); IV) 1100F associated with a MW at 225 ppm F (FT + MW 250F); and V) 1100F associated with a MW at 100 ppm F supplemented with 0.4 % TMP (FT + MW 100F-TMP). The blocks were treated twice a day, undergoing 5 pH cycles over 7 days. Thus, the percentage change in surface hardness (%SH), integrated subsurface hardness loss (ΔKHN), and the concentration of F, phosphorus (P), and calcium (Ca) in the enamel were determined. The data were submitted to ANOVA and Student-Newman-Keuls test (p < 0.001). The 1100F group was statistically inferior to the groups associated with MW for %SH, ΔKHN, and the concentration of P and Ca in the enamel (p < 0.001). Blocks treated with FT + MW 225F and FT + MW 100F-TMP showed significantly lower %SH compared to the other groups (p < 0.001). The FT + MW 100F - TMP group exhibited the lowest depth mineral loss (ΔKHN), and higher concentration de P in enamel (p < 0.001). The adjunct use of MW with FT produces a greater protective effect in inhibiting enamel demineralization, and the supplementation of TMP to the MW with 100F provides a superior effect compared to MW with 225F. This combination of treatments could be regarded as one of several alternative fluoride supplements for subjects at elevated risk of caries.